Hemlock Grove. Season one [videorecording (DVD)] - Roth, Eli, 1972-; Janssen, Famke, 1964-; Taylor, Lili; Liboiron, Landon; Skarsgård, Bill; McGreevy, Brian, 1983- ([Publisher not identified], 2014)
In the shadows of a rusted Pennsylvania steel town, the mangled body of a teenage girl is discovered. As they hunt for a monster among them, rumors mount and many of the eccentric residents become suspects, from the newly-arrived gypsy family to the wealthy Godfrey clan. In the twisted world of Hemlock Grove, everyone hides a dark secret.